Effectiveness of self‐management interventions in young adults with type 1 and 2 diabetes: a systematic review and meta‐analysis. Issue 2 (5th December 2019) - Wong, S. K. W.; Smith, H. E.; Chua, J. J. S.; Griva, K.; Cartwright, E. J.; Soong, A. J.; Dalan, R.; Tudor Car, L.
Abstract: Aim: Diabetes in young adulthood has been associated with poor outcomes. Self‐management is fundamental to good diabetes care, and self‐management interventions have been found to improve outcomes in older adults. We performed a systematic review and meta‐analysis to assess the effectiveness of self‐management interventions in young adults (aged 15–39 years) with type 1 or type 2 diabetes. Methods: We searched five databases and two clinical trial registries from 2003 to February 2019, without language restrictions. We included randomized controlled trials (RCTs) comparing the effectiveness of self‐management interventions with usual care or enhanced usual care in young adults. Outcomes of interest included clinical outcomes, psychological health, self‐care behaviours, diabetes knowledge and self‐efficacy. Pairwise meta‐analysis was conducted using a random effects model and quality of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) criteria. We followed Cochrane gold standard systematic review methodology and reported this systematic review according to PRISMA guidelines. The protocol was registered with PROSEPRO (CRD42018110868). Results: In total, 13 studies (1002 participants) were included. Meta‐analysis showed no difference between self‐management interventions and controls in post‐intervention HbA1c levels, BMI, depression, diabetes‐related distress, overall self‐care, diabetes knowledge and self‐efficacy. Quality of evidence ranged from very low to moderate due to study limitations, inconsistency and imprecision. Conclusions: Current self‐management interventions did not improve outcomes in young adults with diabetes. Our findings, which contrast with those from systematic reviews in older adults, highlight the need for the development of more effective interventions for young adults with diabetes. What's new?: Previous systematic reviews and meta‐analyses on self‐management interventions in type 1 and type 2 diabetes have been conducted in adults of a wide age range and have found improved glycaemic control. No systematic review and meta‐analysis has been conducted in young adults with diabetes. Our meta‐analysis found that existing self‐management interventions did not improve glycaemic control, self‐care behaviours, psychological well‐being, self‐efficacy or diabetes knowledge in young adults with type 1 or type 2 diabetes when compared with controls. There is an urgent need for more effective self‐management interventions for young adults with type 1 and type 2 diabetes.